KORELASI MINAT DENGAN HASIL BELAJAR PESERTA DIDIK PADAPEMBELAJARAN IPA DI SEKOLAH DASAR - Vini Wela Septiana; Sekar Harum Pratiwi; Fiona Rozalina (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
This research is based on the results of observations, a phenomenon that researchers found in one of the problems in science learning, the lack of interest in learning in students, this can be seen from, 1) low science learning outcomes. 2) student records are not complete. 3) playing with a classmate, and 4) doing other activities and some are. 5) cool to draw when the teacher explains the lesson 6) there is no question and answer during the learning process, and. 8) Questions and answers are only done when the learning is finished. The formulation of the problem in this research are: 1) What is the description of students' interest in learning, 2) How is the description of student learning outcomes, 3) Is there a relationship between interest in learning and science learning outcomes for grade IV SD Negeri 03 Tapan, Pesisir Selatan Regency. Objective 1 ) To find out the description of students' interest in learning. 2) To find out about the description of student learning outcomes. 3) To find out the relationship between interest in learning and student learning outcomes in class IV subjects at SD Negeri 03 Tapan, Pesisir Selatan Regency. The hypothesis of this research is that there is a significant relationship between interest and student learning outcomes in science subjects. This study uses quantitative methods, namely connecting between two variables using numbers. Learning Interest variable (X) and science learning outcomes is a variable (Y). The population in this study was the fourth grade students of SD Negeri 03 Tapan, Pesisir Selatan Regency, amounting to 40 people, because the population in this study was small, the researchers took all of the population as samples, namely 40 people, so this study is called population research. The results of this study are: (1) Interest in learning of students at SD Negeri 03 Tapan Pesisir Regency is included in the very high classification. (2) the fourth grade science learning outcomes of SD Negeri 03 Tapan, Pesisir Selatan Regency are classified as High, (3) there is a significant relationship between learning interest and the fourth grade science learning outcomes of SD Negeri 03 Tapan, Pesisir Selatan Regency in the 2-tailed correlation test where the price r count is greater than r table. Conclusions 1) the description of students' interest in learning is classified as very high, 2) the description of student learning outcomes is classified as high, and 3) there is a significant relationship between interest and student learning outcomes in science subjects for class IV SD Negeri 03 Tapan . The researcher's suggestion after doing this research is that the principal, teachers and parents can provide direction, guidance, attention, motivation, and learning facilities in order to achieve educational goals and obtain and can improve maximum learning outcomes